Surface measures on Banach manifolds with uniform structure - Bogdanskii, Yu. V.; Moravets’ka, E. V. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We propose a method for the construction of associated measures on the surfaces of finite codimension embedded in aBanach manifold with uniform atlas.